Parenchymal neuroinflammatory signaling and dural neurogenic inflammation in migraine - Şefik Evren Erdener (BMC, 2021)
Abstract Background Pain is generally concomitant with an inflammatory reaction at the site where the nociceptive fibers are activated. Rodent studies suggest that a sterile meningeal inflammatory signaling cascade may play a role in migraine headache as well. Experimental studies also suggest that a parenchymal inflammatory signaling cascade may report the non-homeostatic conditions in brain to the meninges to induce headache. However, how these signaling mechanisms function in patients is unclear and debated. Our aim is to discuss the role of inflammatory signaling in migraine pathophysiology in light of recent developments. Body Rodent studies suggest that a sterile meningeal inflammatory reaction can be initiated by release of peptides from active trigeminocervical C-fibers and stimulation of resident macrophages and dendritic/mast cells. This inflammatory reaction might be needed for sustained stimulation and sensitization of meningeal nociceptors after initial activation along with ganglionic and central mechanisms. Most migraines likely have cerebral origin as suggested by prodromal neurologic symptoms. Based on rodent studies, a parenchymal inflammatory signaling cascade has been proposed as a potential mechanism linking cortical spreading depolarization (CSD) to meningeal nociception. A recent PET/MRI study using a sensitive inflammation marker showed the presence of meningeal inflammatory activity in migraine with aura patients over the occipital cortex generating the visual aura. These studies also suggest the presence of a parenchymal inflammatory activity, supporting the experimental findings. In rodents, parenchymal inflammatory signaling has also been shown to be activated by migraine triggers such as sleep deprivation without requiring a CSD because of the resultant transcriptional changes, predisposing to inadequate synaptic energy supply during intense excitatory transmission. Thus, it may be hypothesized that neuronal stress created by either CSD or synaptic activity-energy mismatch could both initiate a parenchymal inflammatory signaling cascade, propagating to the meninges, where it is converted to a lasting headache with or without aura. Conclusion Experimental studies in animals and emerging imaging findings from patients warrant further research to gain deeper insight to the complex role of inflammatory signaling in headache generation in migraine.